2015
DOI: 10.1210/en.2015-1718
|View full text |Cite
|
Sign up to set email alerts
|

The Placental Variant of Human Growth Hormone Reduces Maternal Insulin Sensitivity in a Dose-Dependent Manner in C57BL/6J Mice

Abstract: The human placental GH variant (GH-V) is secreted continuously from the syncytiotrophoblast layer of the placenta during pregnancy and is thought to play a key role in the maternal adaptation to pregnancy. Maternal GH-V concentrations are closely related to fetal growth in humans. GH-V has also been proposed as a potential candidate to mediate insulin resistance observed later in pregnancy. To determine the effect of maternal GH-V administration on maternal and fetal growth and metabolic outcomes during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 93 publications
2
17
0
Order By: Relevance
“…6,9 We and others have demonstrated that transgenic expression or administration of exogenous GH-V causes insulin resistance in mice. [10][11][12] A positive association between maternal GH-V and foetal growth has been found in previous studies. [13][14][15] Increased maternal GH-V concentrations were also observed in large for gestational age (lGA) pregnancies.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…6,9 We and others have demonstrated that transgenic expression or administration of exogenous GH-V causes insulin resistance in mice. [10][11][12] A positive association between maternal GH-V and foetal growth has been found in previous studies. [13][14][15] Increased maternal GH-V concentrations were also observed in large for gestational age (lGA) pregnancies.…”
Section: Introductionsupporting
confidence: 58%
“…10,17 Previously we treated both pregnant and non-pregnant female mice with recombinant GH-V and found that GH-V reduced maternal insulin sensitivity in a dose-dependent manner. 11,12 We therefore hypothesized that the maternal serum GH-V would also be altered in GDM pregnancies. However, a direct diabetogenic effect…”
Section: Discussionmentioning
confidence: 99%
“…GH may also be important for modulating pancreatic insulin production (Billestrup and Nielsen, 1991 ; Brelje et al, 1993 ). However, GH from the placenta appears to be primarily important in the acquisition of insulin resistance and shifting metabolic fuel use from glucose to lipid in the mother during pregnancy (Table 1 ; PRL/PL/GH; Horber and Haymond, 1990 ; Goodman et al, 1991 ; Galosy and Talamantes, 1995 ; Barbour et al, 2002 ; Dominici et al, 2005 ; Boparai et al, 2010 ; Liao et al, 2016b ; Sairenji et al, 2017 ). Placental GH reduces insulin receptor expression and signaling, as well as, diminishes the abundance of the insulin-sensitive glucose-transporter, GLUT-4, in the skeletal muscle (Barbour et al, 2004 ; Kirwan et al, 2004 ).…”
Section: Placental Hormones That Mediate Maternal Adaptations To Pregmentioning
confidence: 99%
“…Although growth hormone (GH) has not been generally associated with the metabolic changes during pregnancy, several studies suggest that GH signaling is capable of affecting the maternal organism (7,32,50,51). First, GH and prolactin share a similar intracellular signaling cascade, which is largely dependent on the activation of signal transducer and activator of transcription 5 (STAT5) proteins (19,30,75).…”
Section: Introductionmentioning
confidence: 99%